Influence of Proton‐Pump Inhibitors on the Luminal Microbiota in the Gastrointestinal Tract. Issue 6 (June 2015) - Tsuda, Ayumi; Suda, Wataru; Morita, Hidetoshi; Takanashi, Kageyasu; Takagi, Atsushi; Koga, Yasuhiro; Hattori, Masahira
Abstract : OBJECTIVES: : The objective of this study was to investigate comparatively the influence of proton‐pump inhibitors (PPI) administration on three bacterial communities in the oral cavity, stomach, and colon along the alimentary tract. METHODS: : Forty‐five subjects including 18 patients taking PPI were enrolled. Stimulated saliva, gastric fluid (GF), and feces were obtained from each subject for the microbiota analysis through bacterial 16S rRNA gene profiling using the pyrosequencing method. RESULTS: : The species richness (alpha diversity) was similar among these three microbiota, whereas the interindividual diversity (beta diversity) was much higher in the fecal microbiota compared with that in the others. The UniFrac analysis indicated that the salivary and GF microbiota were similar to one another; however, both differed greatly from the fecal microbiota in the overall bacterial community structure. In the comparison between PPI‐users and PPI‐nonusers, a bacterial cell number increase of ˜1, 000 times was found in the GF of PPI‐users using culturing methods, whereas the bacterial number and composition were nearly identical between the two groups using quantitative PCR and a similarity search based on 16S profiling. The beta diversity significantly increased in both the salivary and GF microbiota of PPI‐users compared with PPI‐nonusers. CONCLUSIONS: : These results suggest that the GF microbiota has recently moved from the saliva. Bacterial overgrowth in the GF by PPI administration may be due to a lack of killing rather than proliferation of the bacteria in the acid‐suppressed stomach. The biological significance of the increase in beta diversity by PPI administration remains unclear.